THE ROLE OF PSYCHOLINGUISTICS IN TEACHING AND LEARNING LANGUAGE. (ESL) - Shermamatova , Zaynab Azimjonovna; Baxriddinova , Dildora Dilshodovna; Baxriddinova , Dildora Dilshodovna; Qironova , Mohigul Bobir qizi (Educational Research in Universal Sciences, 2023)
This article defines psycholinguistics and provides information about its connection with teaching, and gives information about its use during learning and teaching. Moreover it studies types and departments of psycholinguistics and opinions of scientists in this field. Additionally, example and theoretical ideas are presented about methods using techniques and their implementation through psycholinguistics.